Otoritas Keagamaan Baru: Habituasi dan Arena Dakwah Era Digital - Haryadi, Didid (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2020)
The presence of the hijrah community in Indonesia directly resulted in the emergence of a new religious authority. Social media is a key factor in the massive campaign and regeneration carried out by the hijrah community. 'Terang Jakarta' and 'Shift Bandung' are two hijrah communities that have a very large number of congregations, especially on social media. This research attempts to answer the role of social media in shaping new patterns of new religious authority and to describe its relationship with traditional religious authority. Using a qualitative approach, this research finds that the formation of new religious authorities is more dominated by the prseference for preaching through social media, both by public figures and new religious teachers at the local level. These new religious authorities were actively involved in the hijrah community which they directly cultivated. Traditional religious authorities such as Nahdlatul Ulama (NU) and Muhammadiyah need to synergize programs with hijrah groups, especially in dakwah activities and religious moderation. This research considers that the Islamic Progressive group is an alternative movement capable of providing advocacy to all groups in Indonesia.Keywords: New Religious Authority, Progressif Islam, ‘Terang Jakarta’, ‘Shift Bandung’